The combination of the HDAC1 inhibitor SAHA and doxorubicin has synergic efficacy in triple negative breast cancer in vivo - Yuheng Pang; Runze Shi; Liujia Chan; Yu Lu; Di Zhu; Tong Liu; Meisi Yan; Yuji Wang; Wenjing Wang (Elsevier, 2023)
Vorinostat (SAHA) is a histone deacetylase inhibitor that exerts its effects through epigenetic regulation. Specifically, SAHA can inhibit the proliferation of triple-negative breast cancer (TNBC) cells alone or in combination with other chemotherapeutic agents. Doxorubicin (DOX), a traditional chemotherapeutic drug, exhibits a potent cytotoxic effect on cancer cells while also inducing strong toxic effects. In this study, we investigated the synergistic potential of these two drugs in combination against TNBC. Our results suggested that the combination of these two drugs could enhance the inhibitory effect on cancer cell proliferation, resulting in alterations in cell mitotic phase, and suppression of cancer cell stemness. Moreover, our in vivo study unveiled that when SAHA was combined with DOX, it not only exhibited an inhibitory effect on tumor metastasis but also played a role in regulating the immune microenvironment within tumors. Overall, the combination of DOX and SAHA presents a promising avenue for innovative combination chemotherapy in the context of TNBC.